2022
DOI: 10.3389/fphar.2021.749068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential Use of Serotonergic Psychedelics in Autism Spectrum Disorder

Abstract: Recent clinical and preclinical evidence points towards empathogenic and prosocial effects elicited by psychedelic compounds, notably the serotonin 5-HT2A agonists lysergic acid diethylamide (LSD), psilocybin, N,N-Dimethyltryptamine (DMT), and their derivatives. These findings suggest a therapeutic potential of psychedelic compounds for some of the behavioural traits associated with autism spectrum disorder (ASD), a neurodevelopmental condition characterized by atypical social behaviour. In this review, we hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 138 publications
0
13
0
1
Order By: Relevance
“…This latter finding is in line with reports that this genus is increased in the cecum of a genetic autism mouse model in association with altered social behaviour (Golubeva et al, 2017). These data also suggest the interesting possibility that LSD treatment of rodent models of autism spectrum disorder, or indeed patients, may induce changes in gut microbiota composition that revert it to that more representative of control animals or healthy humans, in conjunction with improvements in social behaviour (Markopoulos et al, 2021; Sigafoos et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This latter finding is in line with reports that this genus is increased in the cecum of a genetic autism mouse model in association with altered social behaviour (Golubeva et al, 2017). These data also suggest the interesting possibility that LSD treatment of rodent models of autism spectrum disorder, or indeed patients, may induce changes in gut microbiota composition that revert it to that more representative of control animals or healthy humans, in conjunction with improvements in social behaviour (Markopoulos et al, 2021; Sigafoos et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Bifidobacterium abundance is decreased in the faeces of children diagnosed with autism spectrum disorder (Coretti et al, 2018; Wang et al, 2011), whereas Bifidobacterium‐ and Lactobacillus‐ based probiotics improve autism spectrum disorder and gastrointestinal symptoms by increasing Bifidobacteria (Shaaban et al, 2018) and GABA and decreasing inflammation (Kong et al, 2022). Therefore, the expansion of Bifidobacterium elicited by LSD could represent a mechanism of psychological and gastrointestinal therapeutic improvement in individuals with autism spectrum disorder (Markopoulos et al, 2021; Sigafoos et al, 2007). The Dubosiella genus was also increased by LSD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a pharmacological fMRI study by Preller et al found that classic psychedelics modulate multiple aspects of social cognition via serotonin 2A receptor agonist activity, and these researchers thus suggest that these substances may treat social impairments related to mental health disorders 40 . Further basic and clinical evidence supports the possibility that classic psychedelics might have a role to play in the treatment of social impairments related to mental illness as well 41 , 42 .…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, many clinical studies carried out in the 60s and 70s investigated the possible use of LSD for the treatment of people with ASD and positive evidence emerged. However, this aspect needs to be investigated further with additional studies and clinical trials [ 29 ]. Different clinical trials also reported a positive effect of LSD in the context of alcohol-related disorders; indeed, a meta-analysis of randomized controlled trials concluded that a single dose of LSD is associated with a significant decrease in alcohol misuse [ 244 ].…”
Section: Claviceps Purpureamentioning
confidence: 99%
“…To date, there have been promising clinical trials of PAP with LSD, psilocybin and ibogaine to combat drug, alcohol and nicotine addiction [ 25 , 26 , 27 , 28 ]. Recently, potential applications have been found in the treatment of anxiety, obsessive compulsive disorders, major depression, autism spectrum disorders, and, finally, in delaying cognitive decline [ 27 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%